Economic Empowerment of Women Through Productive Zakat (Analysis of Women’s Entrepreneurship Funding Programs at Rumah Zakat) - Saadah, Chuzaimatus; Ghummiah, Sivi Mala (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2023)
The analysis report of the National Fiscal Policy Agency for December 2022 stated, currently, women in Indonesia will make up around 49.2 percent of the total population in Indonesia in 2021. 53.6 percent of them are of productive age. Meanwhile, women's access to financing from formal financial institutions for micro, small, and medium enterprises (MSMEs) owned by women is currently only around 27 percent. So we need another alternative to providing business opportunities for women. Indonesia Zakat Outlook 2021 mentioned the potential for zakat to reach IDR 327.6 trillion. Therefore, the distribution of zakat has the potential to support the achievement of gender equality and women's empowerment if managed properly. LAZNAS Rumah Zakat, since 2019, has had a female entrepreneur fund the program through productive zakat. Therefore, it is interesting to study the mechanisms and impacts of the utilization of zakat on female beneficiaries. The research that researchers will do uses qualitative research methods that use primary sources in the form of final program reports from Rumah Zakat. The results of the research show that, through the women's entrepreneurship funding program, which consists of cash assistance and technical assistance, it has a positive impact on beneficiary women, especially technical assistance, which has proven to be able to increase the number of unpaid workers with lots of family participation. In addition, this program has been proven to increase the profits of the majority of entrepreneurs. So that the ideals of productive zakat are the long-term welfare of beneficiary women, turning them into muzakki has great potential to be achieved through the Women's Entrepreneurial Funding program by Rumah Zakat.